Pengaruh Model Pembelajaran Inquiry Based Learning Design Berbantu Semi-Soft Scaffoldingterhadap Reduksi Miskonsepsi Siswa pada Materi Kingdom Animalia - Diah Ayu Fatmawati; Nurmiyati Nurmiyati; Ristanti Yustin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The purpose of this research is to ascertain the effect of inquiry based learning design model aided semi-soft scaffolding to reduce student misconception in animalia’s study.The research was considered as quasi experiment research with quantitative approach. The research was designed usingNonrandomized Control Group, Pretest–Posttest Design. The population of this research was all of grade X students at SMA Negeri 1 Boyolali  in academic year 2017/2018 consisting of eight classes. Sample of class selected by cluster sampling. Learning was carried out in two classes by applying the inquiry based learing design model aided semi-soft scaffolding in experiment class Iand discovery learning model in experiment class II. Data collection techniques use four-tier diagnostic test, observations, and documentation. Normality and homogeneity test are performed as a requirement of hypothesis test. Hypothesis test used is t paired test with 5% significance level. Data analysis assisted with SPSS 15. The research procedure includes planning, implementation and data analysis. The conclusion of this research show that  the application of inquiry based learning design model aided semi-soft scaffolding has given effect to reduce 14% student misconception of  grade X students at SMA Negeri 1 Boyolali. The reduction of misconception is greater in the experimental class than the control class by 6%.